Iklan Media Instagram Mempengaruhi Keputusan Pembelian Produk Smartphone Merek Xiaomi di Kota Medan - Wirawan Candra Angkasa; Ngajudin Nugroho; Fauzi Akbar Maulana Hutabarat; Supriyanto; Arwin (Forum Kerjasama Pendidikan Tinggi, 2021)
This study aims to determine the effect of advertising through Instagram social media on purchasing decisions on Xiaomi smartphones. The author uses an associative quantitative method with the sampling technique of incidental sampling, this study uses SPSS to analyze the effect of advertising through social media Instagram with purchasing decisions through questionnaires distributed to 40 respondents, namely the people of Medan Deli District. The results of this study are that there is an influence between advertising through Instagram social media on the purchasing decision of Xiaomi smartphones by 40.7% while the remaining 59.93% is influenced by other factors outside of this study